2019
DOI: 10.1016/j.jsat.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Using nominal group technique to identify barriers, facilitators, and preferences among patients seeking treatment for opioid use disorder: A needs assessment for decision making support

Abstract: Background-The opioid crisis requires rapid scale-up of evidence-based interventions to treat opioid use disorder (OUD), of which pharmacologic therapies with methadone, buprenorphine or long-acting naltrexone are most effective. With recently-developed formulations, there are unprecedented treatment options. Even when pharmacologic treatment is accessible, however, uptake remains low, suggesting individual-level barriers. Decision aids are an evidence-based strategy that may overcome these barriers. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 73 publications
(76 reference statements)
2
40
0
Order By: Relevance
“…Our conceptualization of potential spatial accessibility considers the time travelled to a treatment provider by anyone who suffers an opioid overdose event and may need access to OUD treatment regardless of their grouping by social, economic, demographic or clinical factors [ 15 ]. Previous studies have identified several barriers to accessing OUD treatment, such as convenience of travel time [ 16 ], availability and capacity of treatment providers [ 17 , 18 ] and mode of transportation [ 19 ]. Building on these previous findings and leveraging the spatial turn in health research [ 20 ], we present a method for reconsidering the barriers that exist and addressing them through geographic considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Our conceptualization of potential spatial accessibility considers the time travelled to a treatment provider by anyone who suffers an opioid overdose event and may need access to OUD treatment regardless of their grouping by social, economic, demographic or clinical factors [ 15 ]. Previous studies have identified several barriers to accessing OUD treatment, such as convenience of travel time [ 16 ], availability and capacity of treatment providers [ 17 , 18 ] and mode of transportation [ 19 ]. Building on these previous findings and leveraging the spatial turn in health research [ 20 ], we present a method for reconsidering the barriers that exist and addressing them through geographic considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Select recent evidence from across populations and settings reveals similarities in peoples’ experiences. For example, structural barriers include the costs and convenience of treatment [11, 12], societal stigma [11–13] and the attitudes and behaviours of health care providers [12, 14]. Research has also shown that people’s preferred treatment goals and outcomes are often incongruent with those of the health care system [1517].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies so far to reveal the reasons behind the engagement of OUDs patients in treatment programs. To the best of our knowledge, while some of these studies focused on features of treatment programs as motives for treatment commencement [ 24 , 29 , 35 39 ], few investigated the OUDs associated problems as motives for treatment-seeking [ 5 , 17 , 40 ]. The present study is among the few studies to explore reasons different from treatment programs’ features as motives for treatment-seeking among OUD patients in Iran.…”
Section: Introductionmentioning
confidence: 99%